Some Algebra of Fiscal Transparency : How Accounting Devices Work and How to Reveal Them - Irwin, Timothy (Washington, D.C. : International Monetary Fund, 2012)
Accounting devices that artificially reduce the measured fiscal deficit can be analyzed as transactions involving unrecognized assets and liabilities. Different accounting systems recognize different sets of assets and liabilities and are thus vulnerable to different sets of devices. Some devices can be revealed by moving progressively from cash accounting to modified accrual accounting to full accrual accounting. Revealing all would require the publication of extended fiscal accounts in which all future cash flows give rise to assets or liabilities.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet